Effect of bio-regulators and their time of application on growth and yield of corian- der (Coriandrum sativum) - T Yellamanda Reddy, C Sarada, K Giridhar, (Journal of Spices and Aromatic Crops, 2008)
The effect of plant growth regulators and their time of application on growth and yield ofcoriander was studied during 2004-06 at Regional Agricultural Research Station, Lam, Guntur,Andhra Pradesh. Bioregulators used were NAA (10 & 50 ppm) and triacontonol (e 0.5 mland 1 ml/ litre). Triacontanol @1.0ml/lt recorded maximum plant height, more number ofbranches and more number of umbellets per umbel. NAA @10ppm recorded more number ofumbels per plant and increased crop duration. Maximum seed yield was recorded with NAA@10ppm followed by Triacontanol @1.0ml/lt. With regard to number of sprays two sprays at40 and 60 DAS recorded maximum seed yield, compared to one spray at 40 DAS or threesprays at 40, 60 & 80 DAS